Standing under pressure: hemodynamic effects of abdominal compression type and intensity in healthy adults - Mitra, Kishen; Kunte, Sameer; Taube, Sara; Sankarlinkam, Shruthee; Mohamed, Liban; Adodo, Eghosa; Wu, Kevin A.; Green, Cynthia; Fudim, Marat; Richardson, Eric S. (Frontiers in Physiology, 2025)
IntroductionAbdominal compression is recommended to manage orthostatic intolerance in dysautonomia, but the hemodynamic effects of different compression parameters remain poorly understood. This study investigated how surface area and pressure magnitude of abdominal compression affect blood pressure and heart rate responses during active stand tests in healthy volunteers. Understanding how abdominal compression modulates hemodynamics during standing in healthy individuals will help us better understand how compression can be optimized to benefit those with dysautonomia.MethodsTwo compression devices were developed: one applying circumferential pressure (40 mmHg) over a higher surface area (HSA), and another applying focal pressure to the epigastrium at either 95 mmHg (LSA-LP) or 140 mmHg (LSA-HP). Forty-seven healthy participants completed randomized 3-min active stand tests with each device and a control condition. Heart rate was measured immediately upon standing (0 min) and at 15 s, 30 s, 1 min, 2 min, and 3 min afterward. Blood pressure was measured at 1-min intervals. All measurements were normalized to supine baseline values and presented as mean ± SEM.ResultsAll compression modalities significantly reduced the initial heart rate increase immediately upon standing compared to control (HSA: 2.0 ± 1.1 bpm, LSA-LP: 1.8 ± 1.0 bpm, LSA-HP: 2.7 ± 1.7 bpm vs. control: 6.0 ± 1.2 bpm; all p < 0.01). HSA compression showed greater hemodynamic effects than LSA-LP, with a significantly lower normalized heart rate at 0 min (p = 0.031). HSA compression was associated with higher systolic blood pressure compared to control at 3 min (7.2 ± 0.9 vs. 3.6 ± 0.9 mmHg; p = 0.006), and LSA-HP at 1 min (7.2 ± 1.0 vs. 3.8 ± 1.5 mmHg; p = 0.049). No significant differences were found between LSA-HP and LSA-LP across any timepoint.DiscussionSurface area appears to be a more critical factor than pressure magnitude in stabilizing hemodynamics during orthostatic stress, with significant effects observed immediately upon standing. These findings provide physiological insights for optimizing compression therapy in orthostatic disorders and suggest that wider-area compression garments may offer superior hemodynamic benefits compared to focal compression.